Silicon Fertilizer Application Promotes Phytolith Accumulation in Rice Plants - Sun, Xing; Liu, Qin; Tang, Tongtong; Chen, Xiang; Luo, Xia (Frontiers in Plant Science, 2019)
In this study, a pot experiment was conducted to elucidate the effect of varying dosages of silicon(Si) fertilizer application in Si-deficient and enriched paddy soils on rice phytolith and the carbon (i.e., C) bio-sequestration within phytoliths (PhytOC). The maximum silicon fertilizer dosage treatment(XG3) in the Si-deficit paddy soil resulted in an increase in the rice phytolith content by 100.77% in the stem, 29.46% in the sheath and 36.84% in the leaf compared with a lack of silicon fertilizer treatment(CK). However, WG3 treatment in the silicon-enriched soil increased the rice phytolith content by only 32.83% in the stem, 27.01% in the sheath and 32.06% in the leaf. Overall, Si fertilizer application significantly increased the content of the rice phytoliths in the stem, leaf and sheath in both the Si-deficient and enriched paddy soils, and the statistical results showed a positive correlation between the amount of Si fertilizer applied and the rice phytolith content with correlation coefficients of 0. 998 (p<0.01) in the Si-deficient soil and 0.952 (p<0.05) in the Si-enriched soil. In addition, the existence of phytoliths in the stem, leaf and sheath of rice and its content in the Si-enriched soil were markedly higher than that in the Si-deficient soil. Therefore, silicon fertilizer application helped to improve the phytolith content of the rice plant.